The good and evil serpent: how a universal symbol became christianized - Charlesworth, James H. (The Anchor Yale Bible reference library, 2010)
The serpent of ancient times was more often associated with positive attributes like healing and eternal life than it was with negative meanings. This groundbreaking book explores in plentiful detail the symbol of the serpent from 40,000 BCE to the present, and from diverse regions in the world. In doing so it emphasizes the creativity of the biblical authors' use of symbols and argues that we must today reexamine our own archetypal conceptions with comparable creativity.--From publisher description